DAMPAK POLIGAMI SIRI TERHADAP KEHIDUPAN KELUARGA DI DESA CIGUGUR GIRANG BANDUNG BARAT - Ade Darmawijaya (Asy-Syari'ah, 2019)
Abstarct: In the teachings of Islam Marriage is one form of worship to Allah SWT and follows the sunnah of His Messenger. Marriage for Muslims in Indonesia adheres to the principle of Monogamy, namely - a man marries a woman. However, Law Number 1 of 1974 does not close the meeting door for men who will do marriage with more than one woman (polygamy). This can be done by following the provisions stated in Law No. 1 of 1974. However, the fact in the community is that there are still many polygamous marriages conducted in siri without following the procedures stipulated in the applicable law. so that it is not listed in the State document. So in this study, the motives for polygamy will be revealed, what causes a lot of polygamy siri, how the impact of polygamy siri on family life. The methodology of this study uses the method of observation, interviews, documentation. The results showed that the motives for polygamy included fulfilling sexual desires, showing courage, caring for orphans, elevating women, sharing happiness, continuing the traditions of the ancestors etc. The causes of the occurrence of polygamy siri in his wife did not want to be known by the first wife, the distance to the KUA and Pengandilan Religion was quite far, the polygamy procedure was quite complicated, complicated and expensive, considered insignificant registration of marriage. especially after the first wife was known, administrative problems arose, namely the making of KTP, KK, Birth Certificate, etc., making it difficult to distribute inheritance among family members, emerging vulnerability in the fields of economy, social, education, health and so on.Abstrak: Dalam ajaran  Islam Perkawinan adalah salah satu bentuk ibadah kepada Allah SWT dan mengikuti sunnah Rasul Nya. Perkawinan bagi umat Islam di Indonesia menganut azas Monogami, seorang laki-laki mengawini seorang perempuan. Namun Undang-undang Nomor 1 Tahun 1974 membuka peluang bagi laki-laki yang akan melakukan perkawinan dengan  lebih dari satu orang wanita (poligami). Hal itu dapat ditempuh  dengan mengikuti ketentuan Undang-undang Nomor 1 Tahun 1974. Akan tetapi fakta di masyarakat masih banyak pernikahan poligami yang dilakukan secara siri atau tanpa mengikuti prosedur Undang-undang yang berlaku,  sehingga tidak tercantum dalam dokumen Negara. Penelitian ini akan mengungkap motif melakukan poligami, faktor penyebab banyak terjadi poligami siri, dan bagaimana dampak poligami siri terhadap kehidupan keluarga. Metodologi penelitian ini menggunakan metode observasi, wawancara, dokumentasi. Hasil penelitian menunjukkan bahwa dampak melakukan poligami siri terhadap kehidupan keluarga cukup banyak di antaranya banyak terjadi konflik terutama setelah diketahui isteri pertama, muncul masalah administrasi kependudukan yaitu pembuatan KTP, KK, Akte Kelahiran dsb, mempersulit pembagian warisan di antara anggota keluarga, muncul kerawanan dalam bidang ekonomi, social, pendidikan, kesehatan dan sebagainya.